Síntomas Asociados al Estrés Laboral que Pueden Estar Presentando Los Docentes de La Institución Educativa Distrital San Francisco Sedes B Y C - Luna López, Sol De Jesús; Guzmán Grajales, Marisol (Universidad Antonio Nariño, 2024)
The objective of this research was to analyze the physiological and behavioral symptoms and emotional problems associated with work stress that teachers may be experiencing. San Francisco District Educational Institution. The sample was made up of 31 teachers who work at headquarters B and C of the institution. To collect the data, a questionnaire made up of two parts: investigation of characterization data (age, gender, marital status, number of children, educational level, years teaching, years practicing teaching in the institution and area of ​​performance) and 49 items with YES or NO response options.